Bridging tradition and innovation: a framework for implementing sustainable Design-Build Studios in Middle Eastern architectural education - Abdel Gelil Mohamed, Nermine; Ebaid, May Adel (Frontiers in Education, 2025)
This paper develops and validates the first systematic framework for implementing Design-Build Studios (DBS) in Middle Eastern architectural education. It attempts to close the long-standing gap between theoretical knowledge and practice by aligning regional cultural, environmental, and educational needs with Western design-build precedents. The study follows a multi-stage mixed-methods approach combining the synthesis of systematic literature, framework development, and empirical validation through a detailed survey of 61 regional stakeholders distributed across Egypt, Gulf states, the Levant, Iran, and Turkey. The empirically validated framework sequences DBS implementation into three enabling modules (Curriculum, Studio, People) along three successive stages (Implementation, Operation, Maintenance) with clear integration of Heritage, Sustainability, and Innovation themes. Stakeholder validation records overwhelming regional acceptance (85.2% positive rating) and identifies critical implementation priorities: funding security (67.2% ranked as highest priority), resource availability (59.0%), and participant preparation (54.1%). Regional sustainability priorities are water scarcity (72.1%), affordable housing (68.9%), and heritage preservation (68.9%), which differentiate Middle Eastern requirements from Western precedents. The framework transforms from a conceptual, culturally-adaptive pedagogical model into an empirically-weighted readiness tool that allows systematic institutional assessment across five critical domains (30% funding and feasibility, 20% facilities and resources, 20% community and people, 15% curriculum integration, 15% maintenance and reflection), providing institutions with quantifiable assessment capabilities and prioritized implementation recommendations. This study forms the foundation of DBS implementation, an evidence-based practice where Middle Eastern architectural education can leverage global pedagogic innovations. These are systemically adapted to regional conditions via stakeholder engagement, cultural awareness, and equipping students for the future realities of sustainable and socially responsible architectural practice.